Problematyka moralna w stuletniej (1920-2020) historii „Collectanea Theologica” - Kietliński, Krzysztof (Collectanea Theologica, 2020)
The aim of the publication is to analyse scholarly articles in the field of moral theology in the hundred-year history of “Collectanea Theologica”. It should be noted that this Polish scholarly quarterly has been published since 1920, and until 1930 it was published under the title “Przegląd Teologiczny”. The choice of subjects of theological and moral disputes was strongly influenced by the debates and decisions of the Second Vatican Council, which inspired theologians to study contemporary challenges and look for ways of renewal for individual theological disciplines. The results of their research were the articles in which they analysed current moral issues from an interdisciplinary perspective of both theological and empirical sciences. For this reason, the extensive research material can be divided into eight thematic blocks: historical-moral (22 articles), biblicalmoral (6), philosophical-moral (26), psychological-moral (7), pastoral-moral (9), Catholic social teaching (21), biomedical-moral (6) and the matters to the renewal of moral theology (17). Altogether, in the years 1920-2020, 114 theological-moral articles were published in which such multifaceted issues were examined.